Community hospitals of the future: the role of community hospitals to mitigate health system burden in Singapore - Foo, Chuan De; Chia, Hui Xiang; Tan, Sherianne Yen Tze; Lai, Yi Feng; Khoo, Jia En Joy; Tee, Shi Yun; Lim, Cher Wee; Teo, Ken Wah (Frontiers in Health Services, 2024)
In Singapore, an ageing population with increasing chronic disease burden and complex social circumstances have strained the healthcare system. For the health system to run more efficiently, patients should be appropriately sited according to their medical needs. In Singapore, community hospitals serve as an intermediate inpatient facility managing patients with sub-acute and rehabilitation care needs. Our policy brief uncovers the gaps in transforming community hospital care models and offers actionable steps to unlock the community hospital chokepoints in Singapore's health system. The future community hospitals can accommodate higher acuity but medically stable patients, while patients who do not require inpatient rehabilitation care can be appropriately sited to community partners, if policy, resourcing and technology factors are addressed. An evidence-based, stepwise approach involving all stakeholders will be required to pilot and evaluate new models before large-scale change.